Curriculum Models in Gifted Education: A Comparative Study for 21st-Century Schools - Tyrone O. Gil Jr. (Journal of Education Research, 2025)
The field of gifted education continually seeks effective pedagogical frameworks to foster the intellectual growth, creativity, and socio-emotional development of advanced learners. While numerous curriculum models exist, a comprehensive comparative analysis addressing their practical application and implications for diverse gifted populations remains underexplored. This study addresses this gap by conducting a comparative literature review of prominent curriculum models in gifted education, including the Enrichment Triad Model, Parallel Curriculum Model, Autonomous Learner Model, Maker’s Curriculum Modification Model, The Purdue Three-Stage Model, School-wide Enrichment Model, Talent Search Model, Grid: Depth and Complexity Model, Multiple Menu Model, Integrated Curriculum Model, and Talent’s Unlimited Model. By systematically examining their key features, underlying principles, target learners, and inherent strengths and limitations, this research provides a timely and necessary resource for educators and policymakers. The findings underscore the imperative of aligning curriculum model selection with established gifted education principles and highlight the crucial roles of teachers, parents, gifted learners, and other school stakeholders in this decision-making process. Ultimately, this comparative analysis aims to guide practitioners in making informed choices that maximize student potential and optimize educational outcomes within varied gifted education context. The paper concludes by underscoring the importance of aligning curriculum model selection with gifted education principles and considering the roles of teachers, parents, gifted learners, and other school stakeholders in the decision-making.